A face transgressora da piada : embates entre o riso e a censura - Figueiredo, Sarah Monteiro de Castro Tavares (2015)
This work aims to discuss the transgressor character of the joke, conceiving it as an instrument of socio-political and institutional critique, according as it found the opportunity to contest, covertly, authority figures, despite of social restrictions. The first chapter, entitled A Brief History of laughter in three stages, aims to present the story of laughter along the major historical periods of mankind, namely, the greco-roman Antiquity, the middle ages and modernity. Over the centuries, laughter was the subject of countless debates among politicians and intellectuals about their merits in sociocultural order, always marked by alternating moments of elation and interdiction. In the second chapter, entitled The joke and its vicissitudes in the Freudian discourse, we propose to investigate the problem of jokes on the life and work of Freud. Initially, we address the german and jewish cultural heritage, whose influence proved decisive to attract the interest of the author for the matter concerned. Then we present the status of the jokes in Freud´s work, highlighting two specific texts related to that issue, namely, Jokes and Their Relation to the Unconscious (1905) and Humor (1927). In the third chapter, entitled To the clipboard comrades: clashes between the jokes and censorship in contemporary society, we will analyze some contemporary examples that show this relationship. We emphasize, above all, two satirical tabloids: the Pasquim and the Charlie Hebdo. It should be noted that both weeklies faced a strong censorship by more conservative institutions, notably the military government and religious fundamentalism.